Decentralization: reforms and latin american educative politics in the 90’s - Cortés Arévalo, Olivia; Herrera Pérez, Jhan Carlos; Cortés Arévalo, Olivia; Herrera Pérez, Jhan Carlos; Cortés Arévalo, Olivia; Herrera Pérez, Jhan Carlos (Corporación Universitaria Americana, 2020)
In this article of bibliographic review, the objective is to give relevant information about the reform and educative politics around the decentralization in the educational, political and financial that looks for the quality of the educative system and show the particularities in some countries of the region such as Mexico, Argentina, Chile and Colombia, the efforts that the different governments have made and other actors for rearrange their systems in the last years of the XX century. An documental analysis was made, in which were considered grade works, magazine articles, among other, the results show that there exist poor efficiency of the management of the resources and the acquisition of them to solve many of the problems in levels of quality and coverage in different territorial entities, poor training to the different actors that interpose in the educative process, bad orientation in the profiles and accomplishment of the functions to develop in every one of the scenarios such schools, education secretariats, Ministry of education.